Morphological Regeneration and Functional Recovery of Neuromuscular Junctions after Tourniquet-Induced Injuries in Mouse Hindlimb - Tu, Huiyin; Zhang, Dongze; Corrick, Ryan M.; Muelleman, Robert L.; Wadman, Michael C.; Li, Yu-Long (Frontiers in Physiology, 2017)
Tourniquet application and its subsequent release cause serious injuries to the skeletal muscle, nerve, and neuromuscular junction (NMJ) due to mechanical compression and ischemia-reperfusion (IR). Monitoring structural and functional repair of the NMJ, nerve, and skeletal muscle after tourniquet-induced injuries is beneficial in exploring potential cellular and molecular mechanisms responsible for tourniquet-induced injuries, and for establishing effective therapeutic interventions. Here, we observed long-term morphological and functional changes of the NMJ in a murine model of tourniquet-induced hindlimb injuries. Unilateral hindlimbs of C57/BL6 mice were subjected to 3 hours of tourniquet by placing an orthodontic rubber band, followed by varied periods of tourniquet release (1 day, 3 days, 1 week, 2 weeks, 4 weeks, and 6 weeks). NMJ morphology in the gastrocnemius muscle was imaged, and the endplate potential (EPP) was recorded to evaluate NMJ function. In NMJs, nicotinic acetylcholine receptor (nAChR) clusters normally displayed an intact, pretzel-like shape, and all nAChR clusters were innervated (100%) by motor nerve terminals. During 3 hours of tourniquet application and varied periods of tourniquet release, NMJs in the gastrocnemius muscle were characterized by morphological and functional changes. At 1 day and 3 days of tourniquet release, nAChR clusters retained normal, pretzel-like shapes, whereas motor nerve terminals were completely destroyed and no EPPs recorded. From 1 to 6 weeks of tourniquet release, motor nerve terminals gradually regenerated, even reaching that seen in sham mice, whereas nAChR clusters were gradually fragmented with prolongation of tourniquet release. Additionally, the amplitude of EPPs gradually increased with prolongation of tourniquet release. However, even at 6 weeks after tourniquet release, the amplitude of EPPs did not restore to the level seen in sham mice (13.9 ± 1.1 mV, p < 0.05 vs. sham mice, 29.8 ± 1.0 mV). The data suggest that tourniquet application and subsequent release impair the structure and function of NMJs. Morphological change in motor nerve terminals is faster than in nAChR clusters in NMJs. Slow restoration of fragmented nAChR clusters possibly dampens neuromuscular transmission during the long phase following tourniquet release.